Representing youth with disability on television Glee, Breaking Bad and Parenthood - Hasson, Dana 1980- (New York Peter Lang, 2016)
Representing Youth with Disability on Television is a complex and multidimensional mainstream cultural discourse that examines specific stereotypes in fictional programming. The book draws attention to the group labeled as disabled, which is often marginalized, misrepresented, and misunderstood in the media, by analyzing the popular television programs Glee, Breaking Bad, and Parenthood. To obtain a more rigorous account of the way that youth (9-18 years of age) with disability are framed on television, this analysis examines the following issues: how research on popular culture is contextualized within social theory; the theoretical perspectives on representations of disability in popular culture; and the various contexts, genres, media, representations, and definitions of youth with disability in popular culture. The text also outlines the historical growth of disability, which is crucial for a discussion regarding the changing dimensions of popular culture. Critical hermeneutics, content analysis, and methodological bricolage are the melange of methodologies used to closely examine the dominant models of disability (social vs. medical) used in the portrayal of disabled youth on television today.
Includes bibliographical references (pages 135-147)
Keywords: People with disabilities on television; Youth with disabilities; Youth on television; Sociology of disability; People with disabilities in mass media